A global plastid phylogeny of the brake fern genus Pteris (Pteridaceae) and related genera in the Pteridoideae. (31st July 2014) - Zhang, Liang; Rothfels, Carl J.; Ebihara, Atsushi; Schuettpelz, Eric; Le Péchon, Timothée; Kamau, Peris; He, Hai; Zhou, Xin‐Mao; Prado, Jefferson; Field, Ashley; Yatskievych, George; Gao, Xin‐Fen; et al.
Abstract The brake fern genus Pteris belongs to the Pteridaceae subfamily Pteridoideae. It contains 200–250 species distributed on all continents except Antarctica, with its highest species diversity in tropical and subtropical regions. The monophyly of Pteris has long been in question because of its great morphological diversity and because of the controversial relationships of the Australian endemic monospecific genus Platyzoma. The circumscription of the Pteridoideae has likewise been uncertain. Previous studies typically had sparse sampling of Pteris species and related genera and used limited DNA sequence data. In the present study, DNA sequences of six plastid loci of 146 accessions representing 119 species of Pteris (including the type of the genus) and 18 related genera were used to infer a phylogeny using maximum‐likelihood, Bayesian‐inference and maximum‐parsimony methods. Our major results include: (i) the previous uncertain relationships of Platyzoma were due to long‐branch attraction; (ii) Afropteris, Neurocallis, Ochropteris and Platyzoma are all embedded within a well‐supported Pteris sensu lato; (iii) the traditionally circumscribed Jamesonia is paraphyletic in relation to a monophyletic Eriosorus; (iv) Pteridoideae contains 15 genera: Actiniopteris, Anogramma, Austrogramme, Cerosora, Cosentinia, Eriosorus, Jamesonia, Nephopteris (no molecular data), Onychium, Pityrogramma, Pteris, Pterozonium, Syngramma, Taenitis and Tryonia; and (v) 15 well‐supported clades within Pteris are identified, which differ from one another on molecular, morphological and geographical grounds, and represent 15 major evolutionary lineages.